2022
DOI: 10.1155/2022/4195699
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid Induces the Intestinal Epithelial Barrier Damage through Mitochondrial ROS

Abstract: Mycophenolic acid (MPA) may cause gastrointestinal adverse effects by damaging the intestinal epithelial barrier, the underlying mechanisms remain elusive. Studies have demonstrated that oxidative stress caused by reactive oxygen species (ROS) is linked to tight junction (TJ) proteins and apoptosis, both of which cause abnormalities in intestinal barrier function. Mitochondria, one of the main sources of ROS and abnormally high levels of ROS are linked to mitochondrial dysfunction. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…ROS produced by cells subjected to oxidative stress is a major cause of intestinal barrier dysfunction [ 27 ]. We found that the production of intracellular ROS by cells induced by H 2 O 2 increased significantly to 211.6% ( p < 0.001) of that by untreated cells ( Figure 7 A,B); however, HY7718 treatment led to a significant reduction in ROS levels to 147.6% ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…ROS produced by cells subjected to oxidative stress is a major cause of intestinal barrier dysfunction [ 27 ]. We found that the production of intracellular ROS by cells induced by H 2 O 2 increased significantly to 211.6% ( p < 0.001) of that by untreated cells ( Figure 7 A,B); however, HY7718 treatment led to a significant reduction in ROS levels to 147.6% ( p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…26 Mitochondria are responsible for energy metabolism and ROS production. 27 Alterations in mitochondrial function lead to disrupted energy metabolism and production of damaging ROS. Moreover, mitochondrial dysfunction also disrupts the structure and function of lysosomes.…”
Section: Food and Function Papermentioning
confidence: 99%
“…28,29 Mitochondria maintain cellular homeostasis through their structural and functional plasticity. 27 Mitochondrial structure damage will affect mitochondrial function, leading to rapid production of ROS, ATP consumption, reduction of MMP and mtDNA, and activation of inflammatory bodies. [27][28][29] More and more studies have shown that intestinal mitochondrial dysfunction is one of the important causes of intestinal barrier damage.…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation